An Exploratory Study: Evaluation of the Customer Happiness Based on the Administrative Services Provided by A Low-Cost Airline - Solanki, Kalpana (Archives of Business Research, 2024)
The current research as presented in this report, was carried out on a selected organization, which is Fly Dubai Airlines, operating in the United Arab Emirates (UAE). The aim of the study was to analyse whether the company is offering high quality of administrative services, and how well the services are satisfying and making its customers happy. The study attempted to determine the effectiveness of the administrative services suggest improvement its services over time. A mixed methods research approach was considered for the study, based on which a combination of the qualitative and quantitative data were used. Primary and secondary data collection tools were combined. Primary surveys were conducted with employees of Fly Dubai, including employees in different positions in the company. Of the 100 selected members, 30 responded to the questions that were asked, and their responses were analysed based on a comparative analysis technique by plotting the responses on graphs and charts. Secondary sources such as journals, researched publications, books, and articles were also used to obtain information on the current state of quality performance in the airline sector in UAE. It could be obtained from the findings that Fly Dubai has its focus significantly placed on the factor of quality. High service quality is offered by the company, and the company continuously makes efforts to improve its service quality as well. The quality has been improved over time, and the company follows the ISO standards of quality for measuring the quality levels being provided by the company. Quality Management Systems, Safety Management Systems, and the Flight Data Monitoring (FDM) and Flight Operational Quality Assurance (FOQA) could be found as significantly followed by the company. Customers and their satisfactions are considered as extremely important by the company, and the quality measures of the company are therefore targeted towards achieving improved levels of customer satisfaction. The findings also revealed that there is an overall improvement in quality considered in the airline sector in the region. Quality service could be found as one of the key factors leading to the success of the company too, and hence significant importance being given by the management. Also, a positive link could be found to be existing between the quality of service and operational efficiency of the company, with operations influencing the financial performance of the company as well. At the same time, it could be obtained that the company has scope of improvement too, to consider in its quality approaches, to identify, address and fulfil specific quality preferences of its customers and employees. Accordingly, certain recommendations have been suggested to the company. It has been suggested that the company gives important to every customer and every employee, and try to identify their needs and quality demands, which would help the company to achieve overall quality improvement in its services targeting long term effectiveness of the processes. Also, the company has been recommended to consider an integrated organization-wide data quality management and information governance, as well as focus on continuous improvement in its operations to achieve improved service quality on a continuous basis.